An efficient estimator for population variance using parameters of an auxiliary variable. Issue 6 (18th August 2019) - Yadav, Subhash Kumar; Mishra, Sant Sharan; Gupta, Sat
Abstract: In this work a fresh attempt has been made to search for more efficient estimator for population variance of the study variable by making use of known parameters of an auxiliary variable. There are examples in the literature where authors have used irrelevant auxiliary information such as individual quartiles which have no bearing on variance estimation. In this short paper, we use the known parameters of auxiliary variable in the form of inter quartile range and correlation coefficient with the main variable under consideration. Both of these parameters are clearly relevant to this context. The expressions for the bias and MSE for the intended estimator have been derived using Taylor approximation. A comparison of estimators has been made through numerical computations using natural populations.